Determination Of the Risk Group for The Development of War Syndrome (PTSD) Among the Working Population Against the Background of The Ukrainian-Russian War - Daniil POLIAKOV; Jacek WINIARSKI (Communications of International Proceedings, 2023)
The purpose of the article is to determine the risk group for the development of War Syndrome (PTSD) among the working population against the background of the Ukrainian-Russian war. The developed design of the relevant research involves conducting a relevant survey by means of a questionnaire. The survey is anonymous and involves determining age, gender, level of education, and social status. Also, the key point is to determine the degree of damage by distinguishing the individual symptoms (or their groups) of the syndrome.
Keywords: Post-traumatic stress disorder (PTSD); War Syndrome; Therapy